Time Motion Study of Tuberculosis Patients Attending a Hospital in an Indian State - Manju Toppo; Gursharan S. Mehta; Rashmi Pilkhwal (Preventive Medicine: Research & Reviews, 2025)
Objectives: To analyse the time taken in availing various services by a patient of cardinal symptoms of Tuberculosis in TB Hospital, Bhopal, India and to determine the satisfaction of patients regarding care. Methods: This is a time–motion observational study of patients who came with symptoms of TB. A sample of 210 was calculated using Cochran’s formula. Results: Amongst the 210 patients studied, the majority were males, i.e. 123 (58.6%). A striking feature was found during this study that reports of sputum were given 2–5 days after collection. Conclusion: This busy hospital dedicated to providing comprehensive healthcare pertaining to TB had multiple patient queues, long clinical visits and short clinical encounters. Although the patients were satisfied with the clinical consultations from the doctors, they found difficulty in availing laboratory and X-ray services.